Long-lasting spatial memory deficits and impaired hippocampal plasticity following unilateral vestibular loss. (April 2023) - El Mahmoudi, Nada; Laurent, Célia; Péricat, David; Watabe, Isabelle; Lapotre, Agnès; Jacob, Pierre-Yves; Tonetto, Alain; Tighilet, Brahim; Sargolini, Francesca
Abstract: Unilateral vestibular loss (UVL) induces a characteristic vestibular syndrome composed of various posturo-locomotor, oculomotor, vegetative and perceptivo-cognitive symptoms. Functional deficits are progressively recovered over time during vestibular compensation, that is supported by the expression of multiscale plasticity mechanisms. While the dynamic of post-UVL posturo-locomotor and oculomotor deficits is well characterized, the expression over time of the cognitive deficits, and in particular spatial memory deficits, is still debated. In this study we aimed at investigating spatial memory deficits and their recovery in a rat model of unilateral vestibular neurectomy (UVN), using a wide spectrum of behavioral tasks. In parallel, we analyzed markers of hippocampal plasticity involved in learning and memory. Our results indicate the UVN affects all domains of spatial memory, from working memory to reference memory and object-in-place recognition. These deficits are associated with long-lasting impaired plasticity in the ipsilesional hippocampus. These results highlight the crucial role of symmetrical vestibular information in spatial memory and contribute to a better understanding of the cognitive disorders observed in vestibular patients. Highlights: Unilateral vestibular neurectomy impairs all components of spatial memory. Spatial deficits are associated with impaired learning-associated plasticity in the hippocampus. These results highlight the crucial role of symmetrical vestibular information in spatial memory. They contribute to a better understanding of the cognitive disorders observed in vestibular patients.